Parachromis managuensis : The Danger of Foreign Fish Species in Penjalin Reservoirs - Dadiono, Muh Sulaiman; Murti, Pratiwi Restu (Universitas Tidar, 2023)
Foreign predatory fish species in Indonesia have the potential to threaten the local ecosystem by becoming the main predators that disrupt the balance of the food chain in local waters. Through this research, we want to report the invasion of the species Parachromis managuensis, which originates from Central American waters. This fish species has been found in significant numbers and sizes in the waters of the Penjalin reservoir. In this study, a morphological approach was used to identify the Parachromis managuensis species. The capture of this species was recorded as the first step in efforts to monitor the reservoir water ecosystem in Brebes so that it remains balanced. Results and discussion, including a description of the morphology of the Parachromis managuensis species that have been caught, can be found in this research report.